Las penas de prisión de los delitos aduaneros y su modificación en penas de reclusión en la ley orgánica de aduanas - Armijos Pereira, Eduardo Wualter (2012)
The new Juridical orientation demands modern laws according to society development. It can’t be given priority to some laws while others, that don’t represent political interest, are left behind of the Juridical Legislative discussion. This work involves the urgent reform to the Customs Law because it is confirmed that penalties aren’t enough and they aren’t according to the real situation of Ecuadorian frontiers, breaking legal and constitutional dispositions. The evasion is a phenomenon that affects Collection. In our country where the efficiency in the Tributary Collection has had priority, it is not fair that the customs are neglected, because customs are the most important means of collection due to the existence of a great commercial activity. This research has let me check that the established penalties for the customs transgression don’t keep balance with the damage caused. It isn’t taken into account that in those transgressions the concurrence of others as well as people that participate in those especially civil servants, the most sanctions are from administrative type. The evasion has declined the General Public Budget for years; in the administrative aspect passing from civil to military and vice versa, without radical actions the results continue being the same. The legal deficiency, technological, policies of control as well as lack of collaboration between importers, civil servants and military have become the customs in a political spoil. It’s time to change the Collecting System. As a first action, I propose that the prison penalties must be increased to reclusion and regulated its application, depending on the kind of transgression, applying the principle of proportionality in order to fulfill with the real objective sanctionatory and preventive. This proposal is based on a research program that is detailed in the preliminary step of this work.